Peningkatan Kesadaran Masyarakat Menghadapi Bencana Di Desa Tabing Rimbang Kabupaten Barito Kuala - Rosalina Kumalawati; Astinana Yuliarti; Rizky Nurita Anggraini; Inu Kencana hadi; Karnanto Hendra Murliawan (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2022)
Disasters in South Kalimantan Province did not only occur at the provincial level but also at the village level such as in Tabing Rimbah Village, Mandastana District. Disasters that occur such as floods, fires, and winds. Service activities need to be carried out because they see various areas have the potential for disasters. The purpose of the service is to increase public awareness in dealing with disasters. Service activities are carried out so that public awareness in dealing with disasters increases. The community also becomes more alert and has prepared in dealing with disasters that can occur at any time. Service activities are carried out at the village level because the village is the smallest element in government that has a large enough role in dealing with disasters at the village level. The method used and applied to the service activities of lectures and discussions between participants and resource persons in the field of disaster and disaster communication is active. The people who were invited were representatives of each KK as many as 30 people. The community as participants in service activities is expected to be more active in tackling disasters in Tabing Rimbah Village. Service activities are expected to increase public awareness in dealing with various types of disasters, especially disasters in Tabing Rimbah Village such as floods, fires, and winds that almost routinely occur every year. Awareness raising was carried out through training activities and interactive discussions attended by village heads, community leaders, officials, and the community. The training materials provided are related to types of disasters, how to cope with disasters, knowledge about disaster-resilient villages, and disaster communication. The findings of this service activity are increasing public awareness in dealing with various types of disasters so that people will be more prepared and alert when disasters come so that casualties and property in affected areas can be minimized.